State of art on the role of using a nanofluid in enhancing heat transfer in microchannels with different geometries - Mahmoud G. Abd Elfatah; Osama E. Abd-Ellatif; Ahmed A. A. Attia; Abdelrady O. Elnady (Journal of Engineering and Applied Science)
Abstract Nanofluids in microchannels present a promising solution for enhancing heat dissipation across various engineering applications. This study provide an in-depth analysis of nanofluid role in improving heat transfer efficiency, focusing on critical factors such as nanoparticle concentration, type, and size. The influence of microchannel geometry—such as sinusoidal, square, and circular designs—and the addition of rib structures were also examined. A noticeable increase in the pressure drop was observed across the spectrum of microchannel investigations beyond a concentration threshold of 1 vol. %. Diverging-converging channels demonstrated potential for enhancing heat transfer with minimal pressure drop and pumping power. Most of the reviewed papers have used water and water-ethylene glycol mixtures (65% and 16%, respectively), along with the prevalent use of Al2O3 nanoparticles (37%), underscoring the need to explore alternative base fluids and nanoparticle combinations to achieve optimal performance. The focus on numerical simulations with 61% and 75% single-phase flow in numerical studies highlights the potential to expand research into multiphase flow phenomena. Furthermore, the limited exploration of nanoparticle shape effects and the reliance on simplistic thermal conductivity models point toward avenues for future investigation and model refinement.